Sustainable Educational Space: Contributions to Social Transformation - Rodrigues Siqueira, José Flávio; Zanon, Angela Maria; de Castro Wiziack, Suzete Rosana; Campelo Junior, Marcos Vinicius (Areté, Revista Digital del Doctorado en Educación, 2022)
We detail, in this text, the Sustainable Educator Space concept from the perspective of Transformative Environmental Education. For this, we use critical thinking in the analysis of national official documents that bring this concept and the reflection of Loureiro (2012) to support the emancipatory approach to Environmental Education. As a result, we infer that the official documents, even with textual variations, use the need for the triad physical space, management and curriculum approach for the representation of the concept of sustainable educator space (EES). Still, in this concept, the physical space is reconfigured for better appropriation of environmental goods, as well as for the creation of spaces for interaction and conviviality at school. Management is democratic and participatory and can count on the Environment and Quality of Life Commission for the development of actions and a political-pedagogical project, whereby the curriculum is developed with critical pedagogies and actions in favor of socio-environmental sustainability. Finally, we defend Transformative Environmental Education as a theoretical and methodological support for the transformation of Brazilian public schools into sustainable educator spaces.